If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + 2) = 4 + 5z Reorder the terms: 4(2 + z) = 4 + 5z (2 * 4 + z * 4) = 4 + 5z (8 + 4z) = 4 + 5z Solving 8 + 4z = 4 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 8 + 4z + -5z = 4 + 5z + -5z Combine like terms: 4z + -5z = -1z 8 + -1z = 4 + 5z + -5z Combine like terms: 5z + -5z = 0 8 + -1z = 4 + 0 8 + -1z = 4 Add '-8' to each side of the equation. 8 + -8 + -1z = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -1z = 4 + -8 -1z = 4 + -8 Combine like terms: 4 + -8 = -4 -1z = -4 Divide each side by '-1'. z = 4 Simplifying z = 4
| x+4=-48 | | -68-3= | | 76+6y-35=17y-13-2y | | 8=5-x | | x-3.4=8 | | 3+7x=-15 | | -2(x-3)=4x-3 | | 12=5p+2 | | 13(2r-1)-12r=57 | | 44+30m=99+22m | | 14-6=x | | 2x+(-x)+2x=10+x | | 11x+11=13x-7 | | x^2+10x=1008 | | -3n-18=16 | | 10x-2(4+5x)=8 | | x-3=4x+7+9 | | A=11 | | 7.52=6.28r | | 49r^2-81=0 | | 7y+14x=63 | | 4-.75+.25=l | | x-(4-x)=-15 | | -8+a/6=-3 | | 5y-8=8y-4y | | 4x+2=x+9 | | .75a-3=-9 | | (Y-7)-(y+5)=6y | | 6s^2-13st-5t^2=0 | | 3(2x-8)-(5x-2)=20x-17 | | 4=.75+.25-t | | k^2+12k+20=0 |